Individual Mortality and Macro-Economic Conditions from Birth to Death - Maarten Lindeboom; France Portrait; Gerard J. van den Berg (Tinbergen Institute, 2003)
We analyze the effect of economic conditions early in life on individual mortality rate later in life, using business cycle conditions early in life as an exogenous indicator. Individual records from Dutch registers of birth, marriage, and death, covering a window of unprecedented size (1912-2000) are merged with historical data on macroeconomic and health indicators. We correct for secular changes over time and other mortality determinants. We nonparametrically compare those born in a recession to those born in the preceding boom, and we estimate duration models where the individual's mortality rate depends on current conditions, conditions early in life, age individual characteristics, including individual socio-economic indicators, and interaction terms. The results indicate a significant negative effect of economic conditions early in life on individual mortality rates at all ages.
Keywords: I12; J11; J17; 330; death; longevity; health; business cycle; recession; life expectancy; lifetimes; epidemics; Sterblichkeit; Gesundheit; Konjunktur; Schätzung; Niederlande; Makroökonomischer Einfluss